Requerimentos da Casa Pia e Colégio de Órfãos de São Joaquim: acolhimento social e educação na Bahia do século XIX - Nunes Santos, Erick (2024)
This article presents an analysis of two petitions in which Maria do Carmo Correa requests the admission of her seven-year-old son to the Casa Pia e Colégio de Órfãos de São Joaquim in Salvador. Due to her extreme poverty, she was unable to provide her child with a proper education, leading to her decision to abdicate his custody as an act of resistance. The documents are examined from the perspective of Critical Paleography (PETRUCCI, 2002), Philology (CAMBRAIA, 2005; SPINA, 1994), and the Social History of Written Culture (CASTILLO GÓMEZ, 2003). The research was conducted in the documentary collection of Casa Pia e Colégio de Órfãos de São Joaquim, allowing for the delineation of the socio-economic context of the period under investigation, a social profile of the petitioner, and reinforcing the prestige and social role of the institution in the investigated era. The objectives of this study were to identify, describe, and highlight the information related to individuals who aspire to secure access to quality education for children through the Casa Pia Institution in the city of Salvador, Bahia. The methodological procedures used in the research include documentary and historical research of a qualitative nature. The results reveal the reasons that led families to abdicate their children in pursuit of a good education, highlighting aspects of the penetration and dissemination of written culture in Salvadorian society in the 19th century.